Effect of ball milling conditions on microstructure and lithium storage properties of LiNi0.5Mn1.5O4 as cathode for lithium-ion batteries. (March 2018) - Liu, Cong; Wu, Manman; Liu, Yang; Lu, Zhongpei; Yang, Yang; Shi, Shaojun; Yang, Gang
Graphical abstract: Schematic representation of dry ball-milling (a), wet ball-milling (b) and cyclic performance at 10 C rate. Highlights: Precursors of LNM respectively synthesized by dry and wet ball-milling. Under wet ball-milling raw materials form slurry and mix well in microscale. LNM-w12 sample presents proper stoichiometric composition and the highest DLi + . At 0.1 C rate LNM-w12 delivers 133 mAh g −1 at 100 cycle close to theoretical value. LNM-w12 delivers 97 mAh g −1 at 10 C rate and remains 78% after 1000 cycles. Abstract: In this work, the precursors of LiMn1.5 Ni0.5 O4 (LNM) are respectively synthesized by dry and wet ball-milling. Under wet ball-milling, the problem of sticky residue in dry ball-milling is effectively resolved, the three raw materials form homogeneous slurry and mix well in micrometers level. LNM-w12 sample synthesized by using precursor added 12 mL milling medium gains the atomic composition closed to the theoretical value, ordered crystal structure and the highest lithium diffusion coefficient. At 0.1 C rate, LNM-w12 delivers the capacity of 136 mAh g −1 at the first cycle, and 133 mAh g −1 at the 100th cycle. Moreover, LNM-w12 delivers the initial capacity of 97 mAh g −1 at 10 C rate, and remains 78% after 1000 cycles. The great rate capability of LNM-w12 can be attributed to the well-formed crystal structure, ordered and stable surface structure, which is conducive to the diffusion of lithium ions and prevents the dissolution of the material at high voltage.